(untitled) (Journal of Forestry, 2024)
In this study, seeds of the Turkish pine (Pinus brutia Ten.) species, which is most widely distributed in Turkey, were collected from the Anamur and Mersin regions in 2005 from four elevations: 0-400, 400-800, 800-1200 and above 1200 meters (m). These seeds were stored at +2-4 ºC and germinated at temperatures of 15, 20 and 25 ºC in 2005, 2010, 2012, 2014, 2016, 2018 and 2020, and the effect of storage time on germination percentage (GP) was investigated. According to the general average, there was no significant change in the GP of the seeds as the storage period increased. However, the effect of storage time on GP varied according to region, elevation and germination temperature. Especially in germination at 20 °C at lower elevations, the GP did not change much at the end of 15 years or largely maintained the 2005 germination rates. In the other zones, 80% of the initial germinations were obtained in most of the zones, although there was a slight decrease at the end of the storage period. At 15 ºC, the declines in germination were very insignificant in the first years in both sections, but became significant in the following years. At 25 ºC, the decline in germination was generally higher than at other germination temperatures, and the declines started from the 5th year onwards, and at the end of 15 years, germination declined between 38.0-61.0%. As a result, after 15 years of storage of Turkish pine seeds, it was observed that at 20 ºC the GP was significantly maintained, while at other germination temperatures, the decline in germination increased as the storage period increased. In the storage of the seeds of the species, the storage period should be determined by considering the region and elevation where the seeds were collected.